2023
DOI: 10.1002/aesr.202300021
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role is Always Better than Single: Ionic Liquid as a Reaction Media and Electrolyte for Carbon‐Based Materials in Supercapacitor Applications

Abstract: The burgeoning energy demand necessitates the demand for alternative sources of energy worldwide. The development and enhancement of energy storage devices are the main focus of researchers for sustainable energy production. Carbon supercapacitors have the potential applicability as a commercial source of power. Carbon‐based materials have been synthesized by utilization of ionic liquids (ILs). ILs exhibit unique properties, making them valuable materials to be utilized as a precursor, template, reaction media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…However, with the increase of ultrasonic treatment time, C A began to show a downward trend, which is presumably caused by the damage of the LPC structure. The highest C A value of LPC samples treated by immersion and ultrasonic activation was about 70 mF cm –2 , which revealed that the physical activation methods mainly promoted the electrolyte absorption of LPC. , …”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, with the increase of ultrasonic treatment time, C A began to show a downward trend, which is presumably caused by the damage of the LPC structure. The highest C A value of LPC samples treated by immersion and ultrasonic activation was about 70 mF cm –2 , which revealed that the physical activation methods mainly promoted the electrolyte absorption of LPC. , …”
Section: Resultsmentioning
confidence: 88%
“…The highest C A value of LPC samples treated by immersion and ultrasonic activation was about 70 mF cm −2 , which revealed that the physical activation methods mainly promoted the electrolyte absorption of LPC. 55,56 Furthermore, we also discussed the influence of three electrochemical activation strategies on the performance of LPC. Specifically, the CV cycle test was carried out at three voltage scanning rates of 20, 50, and 100 mV s −1 until the area of the CV curve region no longer increased.…”
Section: Activation Effect Of Activated Lpcmentioning
confidence: 99%
“…ILs are molten salts with melting points less than 100 °C and have been considered environmentally friendly solvents, making them promising materials for industrial applications. 33 Thomas and his team synthesized porous crystalline COFs via an ionothermal technique. 34 A mixture of molten ZnCl 2 and nitrile was heated at 400 °C, which affords the covalent triazine-based framework (CTF), where ZnCl 2 acts as a solvent and catalyst in a reversible cyclotrimerization reaction.…”
Section: Solvothermal Synthesis the Solvothermal Techniquementioning
confidence: 99%
“…Supercapacitors need an electrolyte that links the two electrodes ionically in addition to having the two electrodes separated by an ion-permeable separator. [174][175][176] The four steps of the vapor phase polymerized (VPP) approach are illustrated in Figure 15A: (1) inking the CP matrix with Fe 3þ oxidant media; (2) water-assisted vacuum vapor step polymerization; (3) flushing the sample to release excess oxidant; and (4) drying of the polymerized CP model and CP matrix. Two VPP operations using the aforementioned phases are experienced by one VPP cycle, which is examined in this paper.…”
Section: Flexible Supercapacitormentioning
confidence: 99%